1999
DOI: 10.1016/s0022-5347(05)68161-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravesical Nitric Oxide Therapy on Cyclophosphamide-Induced Cystitis

Abstract: Intravesical NO donors can suppress CYP-induced bladder hyperactivity. We hypothesize that the effect of NO donors is not due to smooth muscle relaxation, but rather due to an inhibitory effect on bladder afferent pathways that was manifested by an increase in intercontraction interval without changes in contraction amplitude. NO donors may be considered as a possible treatment of CYP-induced and other types of bladder inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 18 publications
5
79
0
3
Order By: Relevance
“…24,25) Moreover, it was reported that endogenous and exogenous NO had inhibitory effects on the sensory afferent nerve activity in the bladder when the bladder was irritated by treatment with cyclophosphamide 7) or capsaicin in rat. 26) These studies support that NO plays physiological and pathophysiological roles in not only the relaxation of the urethra and urethral sphincter during micturition leading to decrease in urinary resistance during the emptying phase, but the suppression of afferent nerve function in the bladder, so that a bladder selective NO-donor without cardiovascular effects may be one of possible targets for medical treatment of LUTS.…”
Section: Discussionsupporting
confidence: 54%
“…24,25) Moreover, it was reported that endogenous and exogenous NO had inhibitory effects on the sensory afferent nerve activity in the bladder when the bladder was irritated by treatment with cyclophosphamide 7) or capsaicin in rat. 26) These studies support that NO plays physiological and pathophysiological roles in not only the relaxation of the urethra and urethral sphincter during micturition leading to decrease in urinary resistance during the emptying phase, but the suppression of afferent nerve function in the bladder, so that a bladder selective NO-donor without cardiovascular effects may be one of possible targets for medical treatment of LUTS.…”
Section: Discussionsupporting
confidence: 54%
“…76 For example, intravesical administration of NO donors suppresses the bladder hyperactivity in animals treated with cyclophosphamide. 77,78 In addition, it has been reported that NO levels are decreased in patients with interstitial cystitis, a clinical syndrome that is characterized by bladder pain, urinary urgency and frequency. 79 Alterations in NO levels could, therefore, affect the excitability of sensory fibers in the urinary bladder.…”
Section: Nitric Oxidementioning
confidence: 99%
“…NO released from afferent nerve or urothelium may play a sensory mechanisms in the lower urinary tract. A study of cyclophosphomide-induced cystitis showed that intravesical administration of NO donor depressed bladder hyperactivity [25]. Oral administarion of L-arginine can result in reduced interstitial cystitis symptoms [26].…”
Section: Discussionmentioning
confidence: 99%